2019
DOI: 10.1177/0363546519865251
|View full text |Cite
|
Sign up to set email alerts
|

Low-Profile Dual Small Plate Fixation Is Biomechanically Similar to Larger Superior or Anteroinferior Single Plate Fixation of Midshaft Clavicle Fractures

Abstract: Background: Limited biomechanical data exist for dual small plate fixation of midshaft clavicle fractures, and no prior study has concurrently compared dual small plating to larger superior or anteroinferior single plate and screw constructs. Purpose: To biomechanically compare dual small orthogonal plating, superior plating, and anteroinferior plating of midshaft clavicle fractures by use of a cadaveric model. Study Design: Descriptive laboratory study. Methods: The study used 18 cadaveric clavicle specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
7
16
1
Order By: Relevance
“…The anteroinferior plate yielded values of 3.18% and 18.91% under axial compressive and cantilever bending modes, respectively. These findings were similar to that of Thomas et al [16], who found that dual plate fixation was biomechanically similar to superior and anteroinferior single plate fixation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The anteroinferior plate yielded values of 3.18% and 18.91% under axial compressive and cantilever bending modes, respectively. These findings were similar to that of Thomas et al [16], who found that dual plate fixation was biomechanically similar to superior and anteroinferior single plate fixation.…”
Section: Discussionsupporting
confidence: 91%
“…However, the dual plate fixation model indicated greater stability for fracture treatment. [10,11,13,14,16]. It is meaningful for surgeons to evaluate the biomechanical performance of implants for the reason of improving the treatment result of clavicle fracture.…”
Section: Micro-motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under cantilever bending, traditional superior plate fixation failed at 55 Nm (577 N at 95 mm). This is favourable to load to failure reported in prior studies: Celestre et al reported failure at 36 Nm (300 N at 120 mm) with 3.5-mm superior locking plates [19], Ziegler et al reported failure at 20 Nm (201 N at 100 mm) with a 3.5-mm superior plate [22], Smith et al reported failure at 18 Nm with a superior precontoured plate [26] and Drosdowech et al reported failure through plate bending at 8 to 22 Nm in a model with an inferior cortical defect [27]. We suspect differences in fixation constructs, clavicle models and testing methodology are likely the source of the substantial interstudy variation observed.…”
Section: Discussionsupporting
confidence: 65%
“…Ziegler et al compared dual mini-fragment plating to traditional unilateral plating in cadaver clavicles with a simulated inferior butterfly fragment [22]. No significant differences in stiffness or strength were observed between dual mini-fragment plating compared to traditional unilateral plating.…”
Section: Discussionmentioning
confidence: 99%